Review of the Monograph: T.Y. Khabrieva “Constitutional Reform in Today's Context” - Andrey A Klishas (RUDN Journal of Law, 2017)
This review evaluates the monograph written by Academician of the Russian Academy of Sciences, Vice-President of the Russian Academy of Science, Doctor of Law, Professor, Director of the Institute of Legislation and Comparative Law under the Government of the Russian Federation, Honored Lawyer of the Russian Federation Talia Y. Khabrieva devoted to the research of constitutional reform in today’s context. Special attention is paid to the substantial aspects of the monograph, the current development of the scientific issues on this subject. The review’s author emphasizes that the reviewed book makes a significant contribution to the synthesizing attitudes about constitutional reform in Russian and foreign science, the conclusions given in the monograph can greatly contribute in the nationbuilding process, to develop potentialapproaches and improving the legislation.